KELEMBAGAAN MADRASAH DI INDONESIA - Abubakar, Isti’anah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Madrasah as a form of innovation from boarding - indegenuos institutional-sampoai currently undertaking in the embodiment of Islamic values in the process of education. This mandate is least visible from the travel of government policy with regard to religious education and madrasas. Nevertheless, served until the current contribution of madrasas is still not maximized, given the complexity of the problems faced. In this discussion, at least remind the need for integration of the spirit of madrasa education and pesantern if you want to survive.